การพัฒนาทรัพยากรมนุษย์กับคุณภาพชีวิตการทำงานของข้าราชการ กรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ - ชูยก, ดาเรศ (Community and Social Development Journal, 2014)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาการพัฒนาทรัพยากรมนุษย์ของข้าราชการกรมการพัฒนาชุมซนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ 2) ศึกษาสถานการณ์คุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ 3) ศึกษาความสัมพันธ์ระหว่างการพัฒนาทรัพยากรมนุษย์กับคุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ และ 4) เสนอแนวทางการพัฒนาทรัพยากรมนุษย์ที่ส่งเสริมคุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ ประชากรในการวิจัยมีทั้งหมด จำนวน 273 คน จากจังหวัดยะลา ปัตตานี และนราธิวาส เครื่องมือที่ใข้ในการวิจัย ได้แก่ 1) แบบสอบถาม 2) แบบสัมภาษณ์เชิงลึก 3) การสนทนากลุ่ม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบความสัมพันธ์ด้วยสถิติสหสัมพันธ์คาโนนิคอล (Canonical Correlation) และการวิเคราะห์เส้นทาง (Path Analysis) จากการศึกษาวิจัย พบว่า 1) แนวทางการพัฒนาทรัพยากรมนุษย์ ประกอบด้วย การบริหารผลการปฏิบัติงานการพัฒนารายบุคคล การพัฒนาองค์การ และการพัฒนาอาชีพ มืความเหมาะสมกับข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้ 2) คุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดชายแดนภาคใต้โดยรวมและรายมิติอยู่ในระดับมาก ยกเว้นมิติสุขภาพอนามัยอยู่ในระดับปานกลาง 3) การพัฒนาทรัพยากรมนุษย์มีความสัมพันธ์กับคุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมซนในพื้นที่ 3 จังหวัดขายแดนภาคใต้ มือยู่ในระดับสูง (r=.794)และ 4) การพัฒนาทรัพยากรมนุษย์ที่ส่งเสริมคุณภาพชีวิตการทำงานของข้าราซการกรมการพัฒนาชุมซนในพื้นที่ 3 จังหวัดขายแดนภาคใต้ ควรมุ่งเน้นการพัฒนาอาชีพโดยการวางแผนอาชีพและการบริหารอาชีพโดยการวิเคราะห์ประเมินศักยภาพความรู้ ความสามารถ และสนับสนุนให้บุคลากรได้พัฒนาความรู้ ทักษะที่จำเป็นต่อการปฏิบัติงานและความก้าวหน้าในสายอาชีพซึ่งมืผลต่อคุณภาพชีวิตการทำงานมิติค่าตอบแทน มิติสภาพแวดล้อมการทำงาน และมิติการพัฒนาความรู้ อันจะเป็นส่วนสำคัญที่ส่งเสริมคุณภาพชีวิตการทำงานของข้าราชการกรมการพัฒนาชุมชนในพื้นที่ 3 จังหวัดซายแดนภาคใต้ HUMAN RESOURCE DEVELOPMENT AND QUALITY OF WORK LIFE OF CIVIL SERVANTS OF THE DEPARTMENT OF COMMUNITY DEVELOPMENT IN THREE SOUTHERN BORDER PROVINCES The purposes of this study were to study: 1) Human Resource Development of Civil Servants within the Department of Community Development in Three Southern Border Provinces, 2) The Quality of Working Life of Civil Servants of the Department of Community Development in Three Southern Border Provinces, 3) The Relationship between Human Resource Development and The Quality of Working Life of Civil Servants within the Department of Community Development in Three Southern Border Provinces, and 4) to propose approaches toward the development of human resources that promotes Quality of Working Life of Civil Servants within the Department of Community Development in Three Southern Border Provinces. The research population is 273 people form Yala, Pattani and Narathiwat Provinces.Tools used in the research are: 1) questionnaires 2) an in-depth interview 3) a focus group interview. Statistics used in the analysis of data are percentage and standard deviation. The relationship between used variables is carried out by Canonical Correlation and Path Analysis. The research study 1) The development of human resources deemed appropriate for Civil Servants of the Department of Community Development in The three southern border Provinces are composed of Career development, Organization development, Performance management and Individual development. 2) The Quality of Working Life of Civil Servants within the Department of Community Development in Three Southern Border Provinces is at a high level except health dimensions at a medium level. 3) The result of hypothesis testing on the relationship between Human Resource Development and the Quality of Working Life of Civil Servants of the Department of Community Development in Three Southern Border Provinces is at a high level (r = .794) and 4) It is proposed that the development of human resources to improve the quality of working life of civil servants of the Department of Community Development in Three Southern Border Provinces is as follows: Organizations should focus on career development, career planning and career management, which need to be analyzed to assess the potential capabilities and supporting personnel to develop the knowledge and skills necessary to work and advance their career that affects the quality of working life compensation dimensions, work environment dimensions and the development of knowledge-dimensions It is essential to promote the Quality of Working Life of Civil Servants of the Department of Community Development in Three Southern Border Provinces.